Real-world outcomes from the UK IBD Registry on second-line biologic therapy following anti-TNF exposure in Crohn’s disease: results from the BISCUITS study - Frederick Taylor; Giorgio Bartalucci; Catherine Gleave; Liz Dobson; Keith Bodger; Susanna Dodd; Stuart Bloom; Alun Passey; Riikka Nissinen; Daniel Wirth; Andreas Duva; Jennifer Lee; et al. (Therapeutic Advances in Gastroenterology)
Background: Selection of second-line therapy in Crohn’s disease (CD) patients after failure of first-line TNFα-inhibitor (TNFi) therapy to optimise outcomes remains challenging in real-world clinical practice. Objectives: This study aimed to provide real-world outcomes of CD patients who failed first-line TNFi therapy and switched to either another TNFi or to a biologic with a different mechanism of action. Patients were stratified as to whether they switched because of primary non-response or secondary loss of response to initial TNFi. Design: Retrospective cohort study. Methods: CD patients whose first biologic therapy was a TNFi and switched to another biologic therapy between 26 August 2015 and 31 March 2021 were identified in records held by the UK IBD Registry. Patients were enrolled at study sites, and data were validated by clinical teams. Patients were grouped as within-class switchers (WCS) if their second-line (index) biologic therapy was another TNFi, or out-of-class switchers (OCS) if their index therapy was vedolizumab or ustekinumab. Patients were followed up for at least 1 year. Time to drug discontinuation and outcomes at 1 year after index therapy start were analysed using Cox regression and binary logistic regression models, before and after baseline covariate adjustment through inverse probability of treatment weighting. Results: A total of 180 adult CD patients were included in the study. OCS were less likely to discontinue index therapy in both unweighted analysis (hazard ratio (HR): 0.64, 95% confidence interval (CI): 0.42–0.96, p  = 0.03) and weighted analysis (HR: 0.58, 95% CI: 0.38–0.90, p  = 0.01), and more likely to show index drug persistence at 1 year in both unweighted analysis (adjusted odds ratio (aOR): 3.66, 95% CI: 1.81–7.67, p  < 0.001) and weighted analysis (aOR: 3.95, 95% CI: 2.04–7.89, p  < 0.001). These findings were consistent across all secondary endpoints of steroid-free and/or surgery-free index drug survival at 1 year. Conclusion: Patients switching from a TNFi to either vedolizumab or ustekinumab exhibited significantly higher rates of drug persistence compared to those switching to another TNFi, particularly among those experiencing primary non-response to the initial TNFi.